Optimizing Performance: A Deep Dive into The Periodization for Elite Female Freestyle Wrestlers - Primbetov Azamat Auyesbayevich (Zien Journals, 2023)
This article examines the tailored periodization strategies crucial for optimizing the performance of elite female freestyle wrestlers. Periodization is a systematic planning of athletic training that involves progressive cycling of various aspects of a training program during a specific period. It is fundamental for peak performance and minimizes the risk of overtraining. The research focuses on the unique physiological and psychological demands placed on female athletes and the customization of training cycles to enhance their performance. Drawing from a combination of empirical research, interviews with coaches, and performance data analysis, the article outlines a periodized training model that addresses the strength, endurance, flexibility, and technical skills required in female freestyle wrestling. It further discusses the timing and integration of rest phases to optimize recovery and performance. The article aims to provide coaches and sport scientists with insights and practical guidelines for developing periodized training programs that align with the competitive calendar and the individual needs of female wrestlers to maintain a high level of performance consistently
Keywords: Periodization; Female Athletes; Freestyle Wrestling